PAI LEARNING BASED ON INDEPENDENT LEARNING IN JUNIOR HIGH SCHOOL BABURROHMAH MOJOSARI CONSTRUCTIVISM PERSPECTIVE - Adi Prayogo; Muhammad Romli (Media Inovasi Pendidikan dan Publikasi, 2024)
Islamic education is an effort made by educators in preparing students to believe in understanding and practicing Islamic teachings through activities in schools. This learning is inseparable from the curriculum and learning methods that facilitate the teaching and learning process. Educators enjoy independence in various fields. Objectives of the study: 1. analyze the planning of independent Pai-based learning at Baburrohmah Mojosari Islamic Junior High School. 2. analyze the implementation and evaluation of independent Pai-based learning at Baburrohmah Mojosari Islamic Junior High School from the perspective of Constructivism. This research uses a qualitative approach with a case study type. Based on the data obtained, the following results were obtained: 1. Islamic education learning planning is based on independent learning at Baburrohmah Mojosari Islamic Secondary School. The first teacher has a forum for Islamic religious education maple teachers called Subject Teacher Deliberation, the second is the use of teaching modules obtained by maple teachers through Subject Teacher Deliberation and modifies them according to the characteristics of students in school. 2. The implementation of independent Islamic education learning based on constructivism perspective is in line through three activities/stages including the first preliminary activity/exploratory stage, the second core activity/restructuring stage, the third closing activity/application stage.